A trial of a cypermethrin ‘pour-on’ insecticide to control Glossina pallidipes, G. fuscipes fuscipes and G. morsitans submorsitans (Diptera: Glossinidae) in south-west Ethiopia - Leak, S.G.A.; Mulatu, W.; Rowlands, G.J.; D'Ieteren, G.D.M. (Cambridge University Press, 1995)
Tsetse populations and trypanosome prevalence in cattle were monitored from 1986 to 1993 in the Ghibe valley, south-west Ethiopia. From January 1991 to December 1993 between 2000 and 4000 cattle were treated at monthly intervals with a synthetic pyrethroid insecticide, cypermethrin (RS-alpha-cyano-3-phenoxybenzyl (1RS)-cis, trans-3(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylate). An approximate dosage of 1 ml per 10 kg bodyweight was used to control tsetse flies (Glossina spp.). Treatments were given as `pour-on' applications along the backlines of animals, using automatic drench-gun applicators. This resulted in a decline of 93 percent in the apparent density of G. pallidipes Austen. A reduction of 83 percent in the apparent density of G. morsitans submorsitans Newsted was also observed. This reduction was associated with a reduction in trypanosome prevalence in cattle over 74 percent in 1993, despite a high level of resistance to all available trypanocidal drugs. The numbers of Stomoxys spp. (Diptera: Muscidae) and Tabanidae were also significantly reduced (P<0.01).